Tercer sector, Estado de Bienestar y política social - Marbán Gallego, Vicente (Política y Sociedad, 2008)
New social risks as the aging, the migratory movements, the inequality of gender, the changes in the familiar structure or the productive relocation, in a context of financial constriction and administrative decentralization of the Welfare state, have lead to an increasing role of the Third Sector in the area of the social policy as well as the debate on the type of collaboration between both. In this text, we have analyzed such a debate and the role of the Third Sector in different stages of social services and in different areas of the social policy as the immigration, the attention to dependent people and the social exclusion